Evaluation of the Affect of Maternal and Neonatal Factors on Cord Blood Parameters? - M Mohyeddin Bonab; Z Goliaei; K Alimoghaddam; A Ghavamzadeh (International Journal of Hematology-Oncology and Stem Cell Research, 2004)
Background: Chronic graft versus host disease (cGVHD) is one of the most serious potential complications of allogeneic bone marrow transplantation. Study design and method: We analyzed the incidence of cGVHD and its associated risk factors in a group of 161 Iranian recipients of HLA-identical sibling transplants, with at least 90 days post-transplantation survival. In the majority of cases (n=73), cGVHD occurred in the first year after the transplant (median 273 days). The actual probability of cGVHD within 1 year was 45.3±7% (CI 95%). Results: In a univariate analysis, the most important risk factor was the type of transplant. Peripheral blood stem cell transplants (PBSCT) showed a significant increase in cGVHD compared with bone marrow transplants (BMT) (RR=2.34, p<0.001). In addition, male recipients were at a greater risk than female recipients (RR=2.08, p=0.004). Other risk factors were the presence of prior acute GVHD (RR=2.37, p=0.04) and the previous acute GVHD grade (p=0.03); The probabilities of cGVHD in patients with grade 0, Ι, ΙІ, ΙΙΙ, ΙV acute GVHD were 24%, 44.7%, 42.6%, m56.8%, 64.3%, respectively. Conclusion: In a multivariate analysis, the only independent predictive factors for the development of cGVHD were the type of transplant (PBSC>BM, p<0.001) and male recipient (p=0.005). The survival rate was 88.8% and there was no significant difference in the probability of survival between BPSCT vs BMT (93.8% vs 86.6%, p=0.5).